Phytochemical Analysis and Bioactivity Evaluation of Ethanolic Exctract of Ironwood (Fagraea fragrans Roxb.) Leaves - Mutiara Anggraini; Harmida Harmida; Juswardi Juswardi; Nina Tanzerina (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Ironwood (Fagraea fragrans Roxb.) has been widely used by the community as a medicinal plant, as well as a cosmetic ingredient. Various parts of the ironwood plant are used for health due to the content of metabolite compounds such as alkaloids, steroids, saponins, quinones, and tannins. In an effort to determine the bioactive metabolite compounds, an analysis was carried out on the ethanol extract of Ironwood leaves using GC-MS. The analysis revealed 131 peaks, with 79 corresponding to identified compounds. Five principal dominant compounds were identified: cis-13-Octadecenoic acid, 5-Hydroxymethylfurfural, n-Hexadecanoic acid, Erythocentaurin, and 5-Benzofuranacetic acid. Most of the metabolite compounds in Ironwood leaves exhibit bioactivity as antioxidants, antimicrobials (antibacterial, antifungal), antivirals, anti-inflammatory, anticancer, antiandrogens, antidiabetics, and other bioactivities. Based on the metabolite compounds and bioactivity, ironwood leaves have great potential to be developed as a source of medicinal and cosmetic ingredients.